The Benson Murder Case - Van Dine, S. S., 1888-1939
This novel opens with the death of playboy stockbroker, Alvin Benson, who is found in his brownstone mansion with a bullet through his head.First on the scene is Philo Vance, amateur detective, who is at once intrigued by the absence of Alvin's toupee and his false teeth.These odd clues set him in pursuit of an elusive murderer.He confronts a host of suspects and uncovers a number of family skeletons in his quest for the truth.S.S. van Dine is the pen name of Willard Huntington Wright (1888-1939) who wrote this novel in 1926.He wrote 13 best-selling crime novels and his amateur detective, Philo Vance was later immortalized on screen by William Powell in "The Canary Murder Case".